Pengaruh Tax Avoidance, Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan: (Studi Empiris Perusahaan LQ-45 Yang Terdaftar di BEI Tahun 2017-2021) - Nilam Anggita; Hari Stiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of tax avoidance, capital structure and company size on firm value. The type of research used in this study is a type of quantitative research. The data source used is secondary data, namely annual reports obtained from the Indonesia Stock Exchange (IDX). The population used in this study is LQ-45 companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The sample selection technique used a purposive sampling technique and obtained as many as 28 companies for 5 years with a total sample data obtained of 45 sample data. The results showed that partially the tax avoidance variable and the capital structure variable had an effect on firm value while the firm size variable had no effect on firm value. While simultaneously the tax avoidance variable, capital structure variable and company size variable affect firm value.